Emerging Themes and Research Directions in Halal Fashion: A Bibliometric Study - Aisya, Sitti; Syamsu, Nur (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2024)
This study aims to explore the trends and developments in Halal fashion studies published in Scopus-indexed journals. This study uses a quantitative method of bibliometric analysis to analyze the characteristics of articles, keywords, abstracts, authors, and related journals. This study analyzed a total of 17 articles written by 50 authors and published in 17 different journals. The results showed that research on the phrase Halal fashion experienced a significant increase from 2009 to 2023. In the source analysis category, the Journal of Islamic Marketing ranks top in Halal fashion publications in terms of impact measurement and total citations. Based on the author analysis category, it was found that Management and Science University and the University of Indonesia were the affiliations of authors who ranked first. The author's country affiliation places Indonesia in the first place, followed by China and Malaysia. In the document analysis category, Echchaibi's work published in 2009 ranked first in terms of citations. In the category of word analysis, the keywords that are widely used by the authors are Halal fashion, hijab, Islam, and Islamic marketing. The research makes a significant contribution to mapping trends in research related to Halal fashion.